NON-ORATIONAL CONTRAST WITH BUT: SUBSTITUTION AND ADDITION - Pezatti, Erotilde Goreti [UNESP]; Fernandes De Paula, Danytiele Cristina [UNESP]; Galvao Passetti, Gabriel Henrique [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2019)
The proposal of this study is to investigate the adversative relationship between phrases and words, from the perspective of Functional Discourse-Grammar (Hengeveld and Mackenzie, 2008). For this theory, in constructions like The work took longer than expected, but it was easy, concession takes place between two non-equipollents discursive acts, being the nuclear discursive act marked with but. This study aims to verify whether expressly and implicitly in the construction the letter is not expressly, but implicitly, divided into small squares (PT89: CartografiaPortuguesa: 49) are discursive acts and what is the type of morphosyntactic process that this phenomenon engenders. It uses as a research universe the materials of the corpus Portuguese oral, developed by the Project Portuguese Spoken: Geographical and Social Varieties. This type of structure can indicate that (1) the speaker presents in the first discursive act an information that is soon refuted and replaced by the information contained in the second discursive act; 2) the speaker feels the need to add information that is supposed to be important for the correct interpretation of the addressee.
Keywords: coordination; adversative; concession; but